THE ROLE OF BUSINESS INCUBATORS AND INNOVATION MANAGEMENT IN INCREASING THE PERFORMANCE OF SMEs IN INDRAMAYU REGENCY - Agus Yudianto; Meddy Nurpratama (Universitas YPPI Rembang, 2023)
Objectives The role of the innovation management business incubator towards the process of innovation and change management towards marketing performance. This type of research is